Reactivation of tuberculosis in hepatocellular carcinoma treated with transcatheter arterial chemoembolization: A report of 3 cases - Kim, Yun Jeung (Baishideng Publishing Group Co., Limited, 2012)
Pulmonary tuberculosis is an opportunistic infection that can be reactivated in immunocompromised conditions, for example, in malignancy or after liver transplantation. Hepatocellular carcinoma (HCC) has a high mortality rate because it is frequently diagnosed at an advanced stage. Although surgical resection is the established curative measure for HCC, it is only feasible for early-stage HCC. Transcatheter arterial chemoembolization (TACE) is the most common treatment modality for patients with unresectable HCC. However, repeated TACE sessions and, occasionally, the tumor itself can further impair the reserve hepatic function and immunity. We report 3 recent cases of HCC with reactivation of pulmonary tuberculosis after TACE.